Hermeneutika Al-Qurān Nasr Hamid Abu Zayd - Lia Afiani (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2021)
Some communities in civilization, especially Muslims, the Qur'an is considered a complete and perfect holy book. The Qur'an is a 'text' that transcends and transcends other 'texts' in history. The concept of text in Nasr Hamid Abu Zayd's study project on the Qur'an is quite significant in bringing him to unravel some aspects that have not been touched by other Qur'anic reviewers. For Nasr, studying the Qur'an as a text will lead to a scientific or objective interpretation. One of the hypotheses that says that the Qur'an is a cultural product (muntij al-tsaqÄƒfi) is actually because the text of the Qur'an on the one hand appears as a dialectical process with Arab culture, and on the other hand creates a culture based on existing realities. By adopting the theory of meaning and significance of texts from ED, Hirsch, Nasr divides the categorization of three levels of meaning, namely the meaning that refers to historical facts that cannot be interpreted metaphorically, meaning that can be interpreted metaphorically, and the meaning of